2021
DOI: 10.1007/s00787-021-01754-1
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: ESCAP CovCAP survey of heads of academic departments to assess the perceived initial (April/May 2020) impact of the COVID-19 pandemic on child and adolescent psychiatry services

Abstract: In the original articles, the last four members' of COVID-19 Child and Adolescent Psychiatry Consortium affiliation were incorrectly published. The correct affiliation are given below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Eine Umfrage von ESCAP in Europa zeigte, dass in vielen Ländern zwar zu Beginn der Pandemie die Behandlung stark beeinträchtigt war, aber im Gefolge die Versorgungsstrukturen wieder verfügbar waren 21 . Auch in Deutschland gab es zu Beginn Einschränkungen, dennoch blieb die Versorgung für psychisch kranke Kinder und Jugendliche bestehen – ambulant und stationär.…”
Section: Versorgungunclassified
“…Eine Umfrage von ESCAP in Europa zeigte, dass in vielen Ländern zwar zu Beginn der Pandemie die Behandlung stark beeinträchtigt war, aber im Gefolge die Versorgungsstrukturen wieder verfügbar waren 21 . Auch in Deutschland gab es zu Beginn Einschränkungen, dennoch blieb die Versorgung für psychisch kranke Kinder und Jugendliche bestehen – ambulant und stationär.…”
Section: Versorgungunclassified
“…These reports are in line with the results from a survey of the Research Academy (RA) of the European Society of Child and Adolescent Psychiatry (ESCAP) that encourages the dual formation as clinician-scientist among CAP trainees [ 19 ]. The CovCAP study assessed, among 168 heads of CAP services in 24 European countries, their subjective perception of the first effects of the pandemic [ 18 ]. Eighty percent of the CAP services reported a major effect on service provision.…”
Section: Changes In Health Care Servicesmentioning
confidence: 99%
“…Of special interest to trainees, learning of how to build a treatment alliance, crucial in CAP for good quality of assessment and shared-decision making, was found to be more difficult and tiring using tele-medicine. The CovCAP study also reported a rapid adoption of telemedicine by 95% of services, despite its sparse use before the pandemic (20%) and the absence of guidelines to accompany these changes [ 18 ].…”
Section: Changes In Health Care Servicesmentioning
confidence: 99%